2011
DOI: 10.1016/j.enpol.2011.03.058
|View full text |Cite
|
Sign up to set email alerts
|

Missing carbon reductions? Exploring rebound and backfire effects in UK households

Abstract: Households are expected to play a pivotal role in reducing the UK's greenhouse gas (GHG) emissions, and the UK Government is encouraging specific household actions to help meet its targets. However, due to the rebound effect, only a portion of the GHG emission reductions estimated by simple engineering calculations are generally achieved in practice. For example, replacing short car journeys by walking or cycling reduces consumption of motor fuels. But this frees up money that may be spent on, for example, pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
169
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(195 citation statements)
references
References 28 publications
(13 reference statements)
6
169
0
Order By: Relevance
“…It's nothing, you -1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 This response also demonstrates further evidence of the well documented rebound effect (Jenkins, 2010;Blackhurst et al, 2011;Druckman et al, 2011. ), whereby a proportion of the money saved from increased energy efficiency is utilised to increase the consumption of energy in the home such that the expected level of bill reduction is not realised.…”
Section: The Installation Process and Post-intervention Benefitssupporting
confidence: 60%
See 1 more Smart Citation
“…It's nothing, you -1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 This response also demonstrates further evidence of the well documented rebound effect (Jenkins, 2010;Blackhurst et al, 2011;Druckman et al, 2011. ), whereby a proportion of the money saved from increased energy efficiency is utilised to increase the consumption of energy in the home such that the expected level of bill reduction is not realised.…”
Section: The Installation Process and Post-intervention Benefitssupporting
confidence: 60%
“…), whereby a proportion of the money saved from increased energy efficiency is utilised to increase the consumption of energy in the home such that the expected level of bill reduction is not realised. In other studies this has been shown to be around 30% (Milne and Boardman, 2000;Druckman et al 2011,). It is important for this effect to be considered in the design of GHG reduction schemes in order to maximise potential GHG reduction, whilst balancing the benefit of the rdman, 2000) in increased warmth to the householder.…”
Section: The Installation Process and Post-intervention Benefitsmentioning
confidence: 99%
“…However, we feel that deepening discussions are very important as part of maturing LCSA approaches. We illustrate this by the example of modelling rebound effects in a life cycle perspective, which has been addressed by several authors (Hertwich 2005 ;Hofstetter et al 2006 ;Thiesen et al 2008 ;Girod et al 2011 ;Druckman et al 2011 ;Font Vivanco and Voet 2014 ). Hertwich ( 2005 ) defi nes the rebound effect as 'a behavioural or other systemic response to a measure taken to reduce environmental impacts that offsets the effect of the measure.…”
Section: Main Challenges Identifi Ed In Lcsa Studies So Farmentioning
confidence: 99%
“…switching from car journey to bicycles) leads to funds spent on other energy-and material-intensive activities (e.g., a long distance fl ight). Economy-wide rebound considers the effects such rebounds might have across the economy (Druckman et al 2011 ). Using the savings generated from increased effi ciencies to invest in projects that aim towards industrial ecology goals could be one way to counter such rebounds (as also discussed by Druckman and Jackson, Chap.…”
Section: Crowdfunding In the Solidarity Economymentioning
confidence: 99%